Academic performance among Malaysian graduates: Before and after. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2006)
Opportunities for a better education in our many public universities arc ever increasing. S rodents who are given the chance to receive higher education in any public university in Malaysia are subsidised by the government and, therefore, are determined by national policies.